Fins of fury - O'Hara, Mo.; Jagucki, Marek (New York : Square Fish/Feiwel and Friends, 2016)
Tom and his friend Pradeep take Frankie, the zombie goldfish, on a camping adventure, and something fishy is going on in the woods.
Horn Book
Horn Book, October 2015
4.9
3-6
3-6
Keywords: Camping -- Juvenile fiction; Goldfish -- Juvenile fiction; Zombies -- Juvenile fiction; Camping -- Fiction; Goldfish -- Fiction; Zombies -- Fiction; Camping -- Fiction; Goldfish -- Fiction; Zombies -- Fiction